Long-distance triathletes` intentions to manipulate energy and macronutrient intake over a training macrocycle - Kopetschny, H.; Rowlands, D.; Popovich, D.; Thomson, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
This study explored the information sources long-distance triathletes used to inform their training and nutrition plans, and evaluated these plans over a training macrocycle. Seventy-four long-distance triathletes completed the online survey. Coaches were the most popular training information source (69%), whereas nonprofessional sources (internet 65%, other athletes 53%) were more popular than nutritionists (29%) for nutrition information. Attributes valued most in an information source were: source prior personal experience, individualized advice, breadth of knowledge, and credibility. Sixty-five percent of participants reported previously manipulating dietary intake to improve performance. Forty-three percent reported carbohydrate loading previously, but only 29% planned to carbohydrate load for their upcoming event. Thirty-six percent of participants planned to reduce carbohydrate intake at some point in training, predominantly early (28%) and toward the end (22%) of their macrocycles. Twenty percent of participants planned to maintain energy intake early, and increase (14%) or maintain energy intake (15%) mid-cycle. Triathletes` training plans showed intentions for concurrent increases in volume and intensity, rather than a classical periodized training progression. Limitations of this study include the lack of diet intake and training data, quantitative comparison with dietary guidelines and high/low carbohydrate classification, and an overrepresentation of women in the study cohort. This research showed the popularity of the internet and other athletes to inform triathletes` nutrition plans, and revealed intentions to reduce carbohydrate intakes alongside training load increases, contrary to professional guidelines. Understanding athletes` intentions and sources of nutrition information is crucial to developing effective nutrition education strategies.